Low-lying excited energy states and structure of deformed nuclei / Noora binti Rosli - Rosli, Noora (2013)
Low-lying excited states and structure of even-even, deformed, rare earth 152,154,156Sm and 156,158,160,162,164,166Dy nuclei are studied. A phenomenological model is used to understand the properties of deformed nuclei. The experimental data are analyzed by theoretical analysis within this model. Major steps in the derivation of cranking model are briefly presented. Harris parameterization for the energy and angular momentum are formulated and analyzed. The inertial parameters for the even-even deformed nuclei are defined using the Harris parameterization. The angular frequency of rotation is derived from the cubic equation of angular momentum. The values of angular frequency (I ) rot w and rotational energy E (I ) rot are calculated for the Sm 152 ,154 ,156 and 156,158,160,162,164,166Dy nuclei at low spin I £10h. The energy spectra of positive-parity states which are in good agreement with the experimental data are presented. Few new states that are not available in the experimental data are predicted. At higher total angular momentum, deviation from the adiabatic theory is shown by the increment of energy difference between theoretical and experimental values. It is found that the non-adiabaticity of rotational energy bands occurred at high spin due to the Coriolis effect. The parameters fitted to the model are calculated. The complete low energy structures of 152 ,154 ,156Sm and 156,158,160,162,164,166Dy isotopes are calculated by taking into account the Coriolis mixing between states. The effect of = + n Kp 1 bands on low-lying ( 0 ) 1 Kp = + ground states, 1 b ( = 0 + ) - 2 K p , 2 b iv ( = 0 + ) - 3 K p , and g (K p = 2 + ) - bands is studied. Larger values of Coriolis interaction matrix elements, , ' ( ) x K K j and the closeness between band head energies, K w induce strong states mixing.